Rancang Bangun Sistem Pendukung Keputusan Seleksi Karyawan Dengan Metode Multi Attribute Utility Theory. - wendi, al; budiarti, lela; mandopa, Andi saputra (Fakultas Teknik, Universitas Wiraraja, 2025)
Decision making involving multiple criteria is often a challenge in the selection process, especially when having to choose the best alternative from a number of candidates. This study aims to build a Decision Support System (DSS) that is able to assist the selection process of the best candidates objectively, structured, and efficiently. The method used is the Multi-Attribute Utility Theory (MAUT), which has the ability to handle multi-criteria decision making with a utility approach, where each criterion is weighted based on its level of importance. This system is designed using the UML (Unified Modeling Language) modeling language to present a clear visual representation of the proposed system. The criteria used in the study consist of 5 criteria, namely: Work experience, education, age, status, and web address. Each alternative is assessed based on these five criteria, then the normalization process and calculation of the total utility value are carried out to determine the final ranking. The respondents or samples in this study consisted of 5 students registered in August 2024, from the five samples used, the highest utility result with code A02 in the name of Ahmad Suhery obtained the highest utility value of 0.6893, so that it was determined as the best alternative in the selection process. This system is expected to be a tool to assist in decision making.